Sertraline induced hyponatremia - BHAT H, DHANANJAY; Thanusubramanian, Harish; O, Balaji (Asian Journal of Pharmaceutical and Clinical Research, 2017)
A 53 year old female patient with a history of carcinoma of the breast in remission and dilated cardiomyopathy on treatment was newly diagnosed with depression. She was started on Sertraline 50mg once a day. 2 days later she developed severe hyponatremia (serum sodium 114mEq/l). Her condition further deteriorated and on the 6th day her medication was stopped and replaced with mirtazapine. Osmolality studies she was diagnosed with SIADH (Syndrome of Inappropriate Antidiuretic Hormone secretion). She was treated with IV sodium chloride for her hyponatremia. At discharge serum sodium levels improved (127mEq/l)Â  and subsequent follow up 4 weeks later showed normal sodium values (138mEq/L) Keywords: Sodium chloride, Syndrome of inappropriate antidiuretic hormone, Serum sodium, Serum osmolarity.